Edukasi Pengembangan UMKM Melalui Kreativitas dan Inovasi: Manajemen Permodalan dan Tata Kelola Keuangan di Desa Pantai Bakti Kabupaten Bekasi - Tambun, Sihar; Nathadiharja, Sri Sukartono; Diansyah, Diansyah (Universitas 17 Agustus 1945 Jakarta, 2025)
This community education activity aims to improve the community's understanding of capital management and financial governance of MSMEs. Creativity and innovation are very important so that capital management and financial governance can support MSME operations well. The educational method used is in the form of counseling. The main material presented is to provide an understanding of capital management and simple financial governance for MSME business forms. As a result, 24% of participants understood the material presented very well and 70% of participants understood the educational material presented in the counseling activity. Thus, the objectives of this community service activity have been achieved well and are able to provide changes in understanding to the community. Through this increase in understanding, it is hoped that it can have a positive impact on the development of MSMEs in Pantai Bhakti Village, Muara Gembong, Bekasi.